Melatonin treatment induces chilling tolerance by regulating the contents of polyamine, γ-aminobutyric acid, and proline in cucumber fruit - Miilion P MADEBO; Si-ming LUO; Li WANG; Yong-hua ZHENG; Peng JIN (Journal of Integrative Agriculture, 2021)
The mechanism of melatonin (MT) induced chilling tolerance in harvested cucumber fruit was investigated at commercial maturity. In this study, cucumber fruits were treated with 100 µmol L–1 MT at 4°C and 90% relative humidity for 15 d of storage. In comparison with the control, cucumber treatment with MT resulted in reduced chilling injury (CI), decreased electrolyte leakage and enhanced firmness. The fruits treated with MT showed higher chlorophyll contents in storage conditions with suppressed chlorophyllase enzyme activity. MT treatment increased arginine decarboxylase (ADC) and ornithine decarboxylase (ODC) enzyme activities. Moreover, enhanced expression of the Cucumis sativus ADC (CsADC) and C. sativus ODC (CsODC) genes resulted in the accumulation of polyamine contents. Similarly, proline levels exhibited higher levels among treated fruits. Meanwhile, the proline synthesizing enzymes △1-pyrroline-5-carboxylate syntheses (P5CS) and ornithine aminotransferase (OAT) were significantly increased, while a catabolic enzyme of proline dehydrogenase (PDH) activity was inhibited by treatment. In addition, MT induced expression of C. sativus OAT (CsOAT) and C. sativus P5CS (CsP5CS) genes. Cucumber fruits treated with MT also exhibited higher γ-aminobutyric acid (GABA) content by enhanced GABA transaminase (GABA-T) and glutamate decarboxylase (GAD) enzyme activities and a higher C. sativus GAD (CsGAD) gene expression. To sum up, the results show that MT treatment enhanced chilling tolerance, which was associated with the regulation of polyamines, as well as proline and γ-aminobutyric acid.